1986
DOI: 10.1095/biolreprod34.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Development as Affected by Relaxin in Three Genetically Selected Frame Sizes of Beef Heifers1

Abstract: Purified porcine relaxin was administered into the cervical os on Day 278 of gestation to determine its effects on pelvic development in three genetically selected frame sizes of primiparous beef heifers. Heifers were categorized as small, medium and large frame based upon their genetic composition. Pelvic height, pelvic width and cervical dilatation were determined from Day 270 to 2 days postpartum. On Day 270, heifers were assigned at random to one of three treatments: vehicle control, n = 16; relaxin once (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…This finding is consonant with a relationship between the transmission of milk-borne factor(s) and the expression of hip dysplasia in genetically predisposed pups. By the very nature of its well-known effects on the connective tissues of the pelvic girdle [22][23][24][25][26][27][28], Rlx might be such a factor. Indeed, an early report suggests that treatment of newborn pups with estrogen and an impure porcine Rlx preparation can induce hip dysplasia [291.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consonant with a relationship between the transmission of milk-borne factor(s) and the expression of hip dysplasia in genetically predisposed pups. By the very nature of its well-known effects on the connective tissues of the pelvic girdle [22][23][24][25][26][27][28], Rlx might be such a factor. Indeed, an early report suggests that treatment of newborn pups with estrogen and an impure porcine Rlx preparation can induce hip dysplasia [291.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicates that a combined treatment of relaxin with cloprostenol or dexamethasone reduced the incidence and severity of dystocia due to increased cervica^. and pelvic relaxation (Musah et al, 1986b) as well as reduced the incidence of retained placenta as reported earlier (Musah et al, 1986a).…”
Section: Induction Of Parturition With Cloprostenol and Relaxin; Firssupporting
confidence: 77%
“…This study indicates that a combined treatment of relaxin with cloprostenol or dexamethasone reduced the incidence and severity of dystocia due to increased cervica^. and pelvic relaxation (Musah et al, 1986b) as well as reduced the incidence of retained placenta as reported earlier (Musah et al, 1986a).The mechanisms by which relaxin may reduce retained placenta are unknown* The maternal and fetal connective tissue in placentome becomes progressively collagenized up to the time of parturition. At the onset of parturition, the tissue of the placentome becomes loose, a process that is essential for expulsion of the fetal membranes (Grunert, 1980).…”
mentioning
confidence: 55%
See 2 more Smart Citations